Mechanical Properties of Steel Fiber-Reinforced Concrete by Vibratory Mixing Technology - Yuanxun Zheng; Xiaolong Wu; Guangxian He; Qingfang Shang; Jianguo Xu; Yikai Sun (Advances in Civil Engineering)
As a kind of important engineering material, steel fiber-reinforced concrete was used widely in civil engineering. Up to now, steel fiber-reinforced concrete was usually produced by the traditional mixing method. For the reason of uniform distribution of fiber, the reinforcement of mechanical properties of concrete was inadequately performed. In this paper, C50 steel fiber-reinforced concrete and C60 steel fiber-reinforced concrete were manufactured by traditional mixing and vibratory mixing methods, respectively, and then, the cube compression test, flexural test, splitting tensile test, and the bending test were carried out. The reinforcement effects of mechanical properties were analyzed by comparing the traditional mixing and vibratory mixing methods. The results show that vibratory mixing can effectively improve the distribution of steel fibers in concrete and can increase the density of steel fiber concrete, and therefore, it effectively improves the mechanical properties of steel fiber-reinforced concrete when compared to the traditional mixing method.